Enhancing Meaning in Life and Psychological Well-Being Among a European Cohort of Young Adults via a Gratitude Intervention - Czyżowska, Natalia; Gurba, Ewa (Frontiers in Psychology, 2022)
Background: Strengthening the sense of meaning in life and psychological well-being brings benefits for mental health. The group particularly vulnerable to mental problems are young adults, therefore the aim of our research was to explore how a gratitude intervention will affect the sense of meaning in life, psychological well-being, general health and perceived stress among them. The research also took into account the issue of expressing gratitude. Method: The study involved 80 young adults (58 women and 22 men) who were randomly assigned to the experimental group that filled out the specially prepared diaries for a week (participants were asked to list three things for which they feel grateful, to whom they are grateful and if and how they expressed their gratitude) or the control group. Participants completed the Meaning in Life Questionnaire (MLQ), the General Health Questionnaire – 28 (GHQ-28), the Perceived Stress Scale (PSS), and the Ryff Scales of Psychological Well-Being (PWBS) twice (before and after intervention). Results: In the experimental group significant increases were observed in three areas of psychological well-being: environmental mastery, relationships with others and purpose in life. The significant decrease was also noted in anxiety/insomnia and depression symptoms as well as in perceived stress. There were no differences in the level of meaning in life. There was a positive relationship between expressing gratitude and meaning in life and psychological well-being. Conclusion: Proposed gratitude intervention has the potential to enhance psychological well-being among young adults, however, it may not be effective in enhancing meaning in life.